Estudo dos desafios e limitações para a implantação da Gestão de Custos em um hospital privado de médio porte do Sul de Minas Gerais: projeto de Intervenção - Keyla de Cássia Barros Bitencourt (2020)
Hospital institutions occupy a critical place in the provision of health services. They are health equipment in the process of redefinition, both in the public and private spheres, where several themes are under debate such as their role in the production of care and in the search for quality, integrality, efficiency and the best use of available resources. This study seeks to meet the expectations of managers and users as well as guide management decisions with regard to the best use of resources in serving the population based on cost information. The objective was to identify the challenges and limitations in the implementation of cost management in a medium-sized private hospital, comparing the scenario found to the literature review carried out, analyzing ways to escape these difficulties and proposing an implementation guide. Bibliographic surveys were carried out through a integrative review and participant observation, with the performance of this researcher at the institution where this research took place. In-depth document analysis was used, observing how information and processes are prepared. In addition, unstructured interviews were carried out through a panel of experts with managers involved in the institution's processes. The applied methodology was exploratory and descriptive, with a qualitative approach, guided by strategic prospecting. As for nature, it is an applied research, which aims to generate knowledge for practical application, aimed at solving specific problems. The information collected culminated in the identification of 13 difficulties common to the vast majority of the experiences reported in the implementation of cost management in hospital institutions, synthesized in the integrative review, being these. a) Conceptual difficulties: lack of interest on the part of those responsible for hospitals, cultural resistance and superficial management control; b) Difficulties in setting objectives: lack of technical and/or specialized personnel who know the dynamics and maintenance of the system, lack of training and awareness, lack of scope of the project, lack of definition of cost drivers and lack of autonomy of the responsible manager ; c) Difficulties in the implementation: difficulty in obtaining information, need to use software, use of consultants, scarcity of resources and large volume of activities. In the institution under study, 10 of the 13 difficulties were found, namely: control of superficial management, scarcity of resources and large volume of activities. As a result, alternative suggestions were presented for each of the difficulties encountered, with the steps described in order to enable the effective implementation both in the researched institution and in other hospital institutions, in a cost management implementation script. It allows cost management to be feasible despite the difficulties encountered. The results produced for the researched institution stand out as the generation of prospective knowledge and the dissemination of the “cost culture” with the managers, directors and administrative staff.